Efecto del Glutaraldehído y amonio cuaternario en el control de Escherichia Coli en la planta incubadora “ESPAM MFL” - Álvarez Bermúdez, Juan Diego (2017)
This investigation was carried out in the incubation plant spam MFL of sock was evaluated the bactericidal effect against Escherichia coli. From Glutaraldehyde to 2% (T1), 3% (T2), and 4% (T3) of concentration against Quaternary ammonium 1.6% "biosentary 904" (T0). The bactericide treatments were applied in this plant by means of a backpack pump spray. The samples were taken using the swab method, in the microbiology laboratory was sown in Mc Conkey Agar using the cross striation technique, the results revealed once the analysis of variance was made the absence of statistical differences Although (T1) showed growth of bacteria in incubator and chicken selection room 3365.5 CFU/ml and 5461 CFU/ml respectively, and (T2) in the hatcher with amounts of 2476.5 CFU/ml, the (T3) did not report the presence of the bacterium in all repetitions , this evidence that in regard to the residual effect the Glutaraldehyde to 4% achieved greater bactericidal efficacy over Escherichia coli, in contrast to T0, Glutaraldehyde to 2%, and 3%. A culture of Escherichia coli was also performed on Mc Conkey Agar for the flood application of the respective treatments and the immediate response mode was assessed. The Tukey test showed significant differences 0.05 between T0 and glutaraldehyde concentrations and although there were no statistical differences, it is confirmed that T4 numerically was the best, which constitutes a product that can be used as bactericide.